SKRINING FITOKIMIA DARI DAUN LIDAH MERTUA (SANSEVIERIA TRIVASCIATA) - Siahaan, Ella Oktavianna; Syahputra, Ricky Andi; Sutiani, Ani; Purba, Jamalum; Pulungan, Ahmad Nasir; Nasution, Zuhairiah (Smart Education, 2025)
Abstract: Sansevieria Trivasciata (snake tongue) is a traditional medicinal plant known to contain various bioactive compounds. This study aims to identify secondary metabolite content and characterize Sansevieria leaf crude extract. Plant samples were obtained from Aekbolon village, North Sumatra, and have undergone a taxonomic identification process. The crude extract was prepared by drying and grinding the leaves. The characterization results showed a water content of 8.5% and a water-soluble extract content of 23.85%, which is in accordance with the quality standards of crude extracts according to the Indonesian Herbal Pharmacopoeia. Extraction was carried out using a maceration method using 96% ethanol for three consecutive days. The resulting thick extract was then tested qualitatively to detect secondary metabolites. The screening results showed the presence of allkaloids, flavonoids, saponins, and steroids, while tannins were not detected. These findings indicate that Sansevieria has potential as a source of natural active ingredients for the development of herbal medicines. Keywords: Sansevieria Trivasciata, Phytochemical Screening, Secondary Metabolites Abstrak: Sansevieria Trivasciata (lidah mertua) merupakan tanaman obat tradisional yang diketahui mengandung berbagai senyawa bioaktif. Penelitian ini bertujuan untuk mengidentifikasi kandungan metabolit sekunder serta melakukan karakterisasi simplisia daun Sansevieria. Sampel tanaman diperoleh dari desa Aekbolon, Sumatera Utara, dan telah melalui proses identifikasi taksonomi. Simplisia disiapkan melalui proses pengeringan dan penghalusan daun. Hasil karakterisasi menunjukkan kadar air sebesar 8,5% dan kadar sari larut dalam air sebesar 23,85%, yang sesuai dengan standar kualitas simplisia menurut Farmakope Herbal Indonesia. Ekstraksi dilakukan dengan metode maserasi menggunakan etanol 96% selama tiga hari berturut-turut. Ekstrak kental yang diperoleh kemudian diuji secara kualitatif untuk mendeteksi metabolit sekunder. Hasil skrining menunjukkan adanya senyawa allkaloid, flavanoid, saponin, dan steroid, sedangkan tanin tidak terdeteksi. Temuan ini menunjukkan bahwa Sansevieria memiliki potensi sebagai sumber bahan aktif alami untuk pengembangan obat herbal. Kata kunci: Sansevieria Trivasciata, Skrining Fitokimia, Metabolit Sekunder